Corporate Social Responbility and Good Corporate Governance On Company Value - Tituk Diah Widajantie; Sofia Yunida Putri (IAIN Kendari, 2022)
The value of the company is the main goal of a company formed. However, in its implementation there are regulations that require companies to have social programs and good corporate governance. This study aims to prove whether there is an effect of corporate social responsibility and good corporate governance on firm value. This research is classified as quantitative research. The population used is SOEs listed on the LQ45 Indonesia Stock Exchange in the 2015-2017 period and with a purposive sampling technique. Data obtained from annual financial reports and sustainability reports. This study uses a quantitative approach with multiple linear regression analysis. The analytical method used is statistical analysis which is calculated using the SPSS (Statistical Package for the Social Sciences) application version 25. The results of this study indicate that: (1) corporate social responsibility has no effect on firm value; (2) good corporate governance has an effect on firm value.